The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fmicb.2022.1068328
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between chicken TRIM25 and MDA5 and their role in mediated antiviral activity against IBDV infection

Abstract: Infectious Bursal Disease Virus (IBDV) is the causative agent of an immunosuppressive disease that affects domestic chickens (Gallus gallus) severely affecting poultry industry worldwide. IBDV infection is characterized by a rapid depletion of the bursal B cell population by apoptosis and the atrophy of this chief lymphoid organ. Previous results from our laboratory have shown that exposure of infected cells to type I IFN leads to an exacerbated apoptosis, indicating an important role of IFN in IBDV pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…In addition, RIG-I is also absent in chickens, which is presumably attributable to their higher susceptibility to NDV compared with waterfowls such as ducks and geese [67,68]. Instead of RIG-I, NDV and other RNA viruses are recognized by the other two RLR family members, MDA5 and LGP2, which preserve antiviral competence in chickens [69][70][71][72][73]. The infection of the virulent genotype VIId NDV strain was accompanied by massive MDA5 expression in the oviducts of egg-laying hens and chicken bone-marrow-derived dendritic cells in the early infection stage [74,75].…”
Section: Receptors For Ndv Pampmentioning
confidence: 99%
“…In addition, RIG-I is also absent in chickens, which is presumably attributable to their higher susceptibility to NDV compared with waterfowls such as ducks and geese [67,68]. Instead of RIG-I, NDV and other RNA viruses are recognized by the other two RLR family members, MDA5 and LGP2, which preserve antiviral competence in chickens [69][70][71][72][73]. The infection of the virulent genotype VIId NDV strain was accompanied by massive MDA5 expression in the oviducts of egg-laying hens and chicken bone-marrow-derived dendritic cells in the early infection stage [74,75].…”
Section: Receptors For Ndv Pampmentioning
confidence: 99%
“…Ref. [ 44 ] Furthermore, the expression of TRIM25 is upregulated after infection with the infectious bursal disease virus (IBDV), which in turn inhibits the replication of the virus [ 45 , 46 ]. Herein, we found that RABV infection also upregulates the expression of TRIM21, but unlike the mentioned viruses, it promotes the replication of RABV.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM25 has been demonstrated to be an RNA-binding protein, which plays a key role in the antiviral interferon response by activating the RIG-I pathway ( Choudhury et al., 2020 ; Xiao et al., 2021 ; Diaz-Beneitez et al., 2022 ). However, new evidence has shown alternative mechanisms for TRIM25 anti-IAV action.…”
Section: Influenza a Virusmentioning
confidence: 99%